Harmony haven: usability evaluation of matrimonial websites for cultural sensitivity in Bangladesh - Hasan, Firoz; Hasan Moon, Md.; Ahmed Momin, Tanvir; Akter, Sumaya; Awal Hadi, Md.; Mamun Raza, Dewan; Al Badhon, Noman (Institute of Advanced Engineering and Science, 2025)
In the digital age, matrimonial websites have become essential platforms for matchmaking, particularly in culturally diverse societies like Bangladesh. This study explores the usability and cultural sensitivity of five popular matrimonial websites—Biyeta, OrdhekDeen, SensibleMatch, Shaadi.com, and Bangladeshi Matrimony—tailored for Bangladeshi users. Using Nielsen's Heuristics, the research identifies key usability issues and cultural misalignments. Data were collected via a questionnaire with 105 respondents, focusing on usability and cultural relevance. The results revealed that OrdhekDeen was the most used platform, with 40% of users preferring it, followed by Bangladeshi Matrimony at 23.8%. Usability issues were categorized, with 46.7% of users reporting challenges in navigating websites and 44.8% finding design consistency lacking. However, error prevention was highly rated, with 54.3% stating they never mistakenly sent messages due to unclear prompts. The study concludes with recommendations for improving cultural alignment and usability to enhance user satisfaction.